The Total of Semicentennial Attention in Armenia to Osip Mandelshtam - GONCHAR, NATALYA; MKHITARYAN, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The collection is composed in commemoration the 125th anniversary of XX century great Russian poet Osip Mandelshtam. It is known, that Armenia, Armenian impressions, motives rank high place in Mandelshtam’s poetry and prose. So a great number of publications, translations, studies, articles, editions devoted to Mandelshtam were created and stored in Armenia from1966th till now. This material is presented in the bibliographical collection. Many components of it are accompanied by annotations, commentary, fragments from most important texts.
Keywords: literary connections, 125th anniversary, collection, half century, author, component, annotation, fragment